Vertical organization, technology flows and R&D incentives: an exploratory analysis - Dietmar Harhoff (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
Despite its importance, the impact of vertical organization on innovation incentives has not been investigated in depth. This paper develops a number of testable hypotheses and then provides a first exploratory empirical analysis, using cross-sectional industry-level data. Two simple stylized facts emerge from the empirical results. First, once a fragmented buyer industry is dependent on a relatively concentrated supply sector, the industry's own R&D intensity is reduced substantially. Second, vertical technology flows appear to act as substitutes for an industry's own R&D if the receiving industry's concentration is relatively low. Both results are largely consistent with a number of case studies and with theoretical arguments discussed in the paper. – – Der Einfluß der vertikalen Organisation von Industrien auf Innovationsanreize ist trotz der Bedeutung der Fragestellung noch nicht detailliert untersucht worden. Dieses Papier stellt eine Reihe von testbaren Hypothesen vor und präsentiert eine erste explorative empirische Analyse auf der Basis eines Querschnittsdatensatzes. Zwei empirische Regularitäten können nachgewiesen werden. Zum einen liegt die FuE-Intensität einer Industrie erheblich unter dem üblichen Durchschnitt, wenn die Konzentration der Industrie niedrig ist, aber eine Abhängigkeit von einer konzentrierten Zuliefererindustrie besteht. Zum zweiten scheinen vertikale Technologieflüsse als Substitute für die eigene FuE einer Industrie zu fungieren, sobald die Konzentration der Empfängerindustrie relativ niedrig ist. Beide Resultate sind prinzipiell konsistent mit weiterer Evidenz aus Fallstudien und mit den theoretisch hergeleiteten Hypothesen.
Keywords: 330